Different Markov chains modulate visual stimuli processing in a Go-Go experiment in 2D, 3D and augmented reality - Mugruza Vassallo, Carlos (2022)
The introduction of Augmented Reality (AR) has attracted several developments, although the people’s experience of AR has not been clearly studied or contrasted with the human experience in 2D and 3D environments. Here, the directional task was applied in 2D, 3D, and AR using simplified stimulus in video games to determine whether there is a difference in human answer reaction time prediction using context stimulus. Testing of the directional task adapted was also done.